Erstlinge Lettischen Drucks – Kristofora Fīrekera rakstība iespiestā veidā - Vanags, Pēteris (Baltistica, 2010)
ERSTLINGE LETTISCHEN DRUCKS – CHRISTOPHOR FÜRECKER’S ORTHOGRAPHY IN PRINTED FORMThis article investigates the issue of Christophor Fürecker’s influence on the development of Latvian orthography in the late 17th century, especially the problem of whether Fürecker’s orthographic system was used in any printed texts.In the light of the evidence adduced, there is good reason to abandon the traditional assertion that the spelling conventions introduced by Fürecker were not used in their printed form.  In the 1760s there appeared, in Besemeser’s printery, a sample of hymn translations (Erstlinge lettischen Drucks) using special conventions, which may well have differed from those used in manuscripts. The edition in question has, however, not been found, and it is therefore not possible to pinpoint any specific details.Certainly in the preparation of the Riga Handbook (1671–1673), Fürecker’s texts were modified to conform more closely to traditional practice: long vowels indicated with a subscript marker were changed to , while (and sporadically as well as ) along with the accent on vowels in the locative and several other elements of Fürecker’s system were maintained.In the hymnal of 1672, the characters , appear for the first time:  they were subsequently legitimised in the orthography of the Bible Commission (1685).  Thus the orthography of Fürecker’s hymns is observable in printed form in the 1671–1673 and 1685 Riga Handbooks: modified, but nonetheless in a usage deriving from his system.
Keywords: latvių kalba; senieji raštai; Fiurikeris; rašyba